Evaluating salivary MMP-8 as a biomarker for periodontal diseases: A systematic review and meta-analysis - Zsuzsanna Domokos; Fanni Simon; Eszter Uhrin; Bence Szabó; Szilárd Váncsa; Gábor Varga; Péter Hegyi; Beáta Kerémi; Orsolya Németh (Heliyon)
Objective: Periodontitis is the irreversible destructive process of the periodontium and is the major cause of tooth loss in adults worldwide. Diagnosis of early-stage periodontal disease is crucial for improving outcomes, and to this end, the application of indicator biomarkers is gaining interest. One such method involves measuring the level of matrix metalloproteinase-8 (MMP-8). This systematic review and meta-analysis aims to evaluate the salivary MMP-8 level of periodontitis and gingivitis cases compared to healthy controls. Data: We evaluated all studies that compared different laboratory techniques for measuring salivary MMP-8 levels in periodontitis and gingivitis patients, alongside healthy controls. Sources: The systematic search was performed on 10 October 2022 in three electronic databases. Study selection results: Pooled mean differences (MD) were calculated with 95 % confidence intervals (CIs) between the researched groups. In addition, the correlation coefficient results between MMP-8 values and other clinical parameters were narratively summarized.Based on 20 eligible studies (n = 1725), patients with periodontitis presented significantly higher MMP-8 levels (MD = 273.26 ng/ml, CI: 194.42; 352.10). Similarly, patients with gingivitis presented significantly higher salivary MMP-8 levels than healthy individuals (MD = 122.82 ng/ml, CI: 64.19; 181.45) based on the results of 10 eligible studies (n = 704). Additionally, we found higher MMP-8 levels in periodontitis compared to gingivitis (MD = 112.04 ng/ml, CI: 56.15; 167.92). The correlation results suggest that salivary MMP-8 is associated with different clinical periodontal parameters. Conclusion: Salivary MMP-8 level measurement may be a reliable method to distinguish between periodontal health and periodontal disease and also to distinguish between gingivitis and periodontitis. Clinical significance: The measurement of salivary MMP-8 levels may have the potential to differentiate between periodontal health and disease reliably. Accordingly, it can be considered for integration into routine dental examinations as a quick and convenient method for the early detection and prevention of periodontitis, pending further validation.